Juridical Review of the Process of Resolving Problem Credit Through Parate Execution - Dewi, Maftuhah (FOCUS: Jurnal of Law, 2023)
This study aims to analyze the mechanism for resolving non-performing loans through parate execution of mortgage rights in accordance with Article 6 of the Mortgage Rights Law. The method used is normative juridical with descriptive analysis approach. The results show that parate execution is a quick and economical solution, but there are obstacles such as third party lawsuits and dispute confiscation that can hinder the process. This research contributes to the understanding of the mechanism of parate execution and offers recommendations for the development of banking policies that are more effective in managing the risk of non-performing loans.